Cicadidae Periostracum, the Cast-Off Skin of Cicada, Protects Dopaminergic Neurons in a Model of Parkinson's Disease. (24th October 2019) - Lim, Hye-Sun; Kim, Joong-Sun; Moon, Byeong Cheol; Choi, Goya; Ryu, Seung Mok; Lee, Jun; Ang, Mary Jasmin; Jeon, Mijin; Moon, Changjong; Park, Gunhyuk
Abstract : Parkinson's disease (PD) is characterized by dopaminergic neuronal loss in the substantia nigra pars compacta (SNPC) and the striatum. Nuclear receptor-related 1 protein (Nurr1) is a nuclear hormone receptor implicated in limiting mitochondrial dysfunction, apoptosis, and inflammation in the central nervous system and protecting dopaminergic neurons and a promising therapeutic target for PD. Cicadidae Periostracum (CP), the cast-off skin of Cryptotympana pustulata Fabricius, has been used in traditional medicine for its many clinical pharmacological effects, including the treatment of psychological symptoms in PD. However, scientific evidence for the use of CP in neurodegenerative diseases, including PD, is lacking. Here, we investigated the protective effects of CP on 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine- (MPTP-) induced PD in mice and explored the underlying mechanisms of action, focusing on Nurr1. CP increased the expression levels of Nurr1, tyrosine hydroxylase, DOPA decarboxylase, dopamine transporter, and vesicular monoamine transporter 2 via extracellular signal-regulated kinase phosphorylation in differentiated PC12 cells and the mouse SNPC. In MPTP-induced PD, CP promoted recovery from movement impairments. CP prevented dopamine depletion and protected against dopaminergic neuronal degradation via mitochondria-mediated apoptotic proteins such as B-cell lymphoma 2 (Bcl-2), Bcl-2-associated X, cytochrome c, and cleaved caspase-9 and caspase-3 by inhibiting MPTP-induced neuroinflammatory cytokines, inducible nitric oxide synthase, cyclooxygenase 2, and glial/microglial activation. Moreover, CP inhibited lipopolysaccharide-induced neuroinflammatory cytokines and response levels and glial/microglial activation in BV2 microglia and the mouse brain. Our findings suggest that CP might contribute to neuroprotective signaling by regulating neurotrophic factors primarily via Nurr1 signaling, neuroinflammation, and mitochondria-mediated apoptosis.